Determinants of Corruption in ASEAN Countries - Li, Li (Archives of Business Research, 2024)
This paper investigates the economic, institutional, and social determinants of corruption in ASEAN countries using unbalanced panel data over the period of 1996–2022. ASEAN has 10 countries, such as Brunei Darussalam, Cambodia, Indonesia, Lao People's Democratic Republic, Malaysia, Myanmar, the Philippines, Singapore, Thailand, and Vietnam. Corruption is measured by the Corruption Perception Index published by Transparency International. Determinants of corruption are expected to be foreign direct investment, gross domestic product per capita growth, inflation, political stability, regulatory quality, and internet usage, based on the literature review. The empirical results show that increasing foreign direct investment, political stability, and regulatory quality in ASEAN countries can reduce corruption significantly, whereas internet usage is found to have a slightly significant positive effect on corruption. However, gross domestic product per capita growth and inflation are not determinants of corruption in ASEAN countries.